2014
DOI: 10.1371/journal.pone.0103115
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Hummock and Hollow Soils of Three Wetlands on the Qinghai-Tibetan Plateau Revealed by 16S rRNA Pyrosequencing

Abstract: The wetlands of the Qinghai-Tibetan Plateau are believed to play an important role in global nutrient cycling, but the composition and diversity of microorganisms in this ecosystem are poorly characterized. An understanding of the effects of geography and microtopography on microbial populations will provide clues to the underlying mechanisms that structure microbial communities. In this study, we used pyrosequencing-based analysis of 16S rRNA gene sequences to assess and compare the composition of soil microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…5). The distribution of methanogens along the elevation gradients was in agreement with their strict anaerobic metabolism (Deng et al 2014b), which was also identified by the RDA (Fig. 6).…”
Section: Archaeal Community Composition Along the Elevationsupporting
confidence: 83%
“…5). The distribution of methanogens along the elevation gradients was in agreement with their strict anaerobic metabolism (Deng et al 2014b), which was also identified by the RDA (Fig. 6).…”
Section: Archaeal Community Composition Along the Elevationsupporting
confidence: 83%
“…There was much lower SOC content in the hollow (7.3 ± 2.2%) than that in the hummock (13.4 ± 0.7%) terrain [Deng et al, 2014].…”
Section: à2mentioning
confidence: 81%
“…Furthermore, the difference in SOC levels between the swamp and swamp meadow (substrate for CH 4 formation) should have fundamentally affected CH 4 emissions; there was a much higher SOC content in the swamp site (18.1 ± 0.4%) compared with the swamp meadow site (9.3 ± 0.6%) in this study. The much higher SOC in a Haibei wetland (~24.5%) [Yu et al, 2013] and Zoige wetland (33.1À39.0%) [Deng et al, 2014], created by higher carbon accumulation under strictly anaerobic conditions [Chen et al, 2014], also largely explains their higher CH 4 emissions (Table 1). Finally, the higher plant biomass in the swamp (565.9 ± 40.6 g m…”
Section: 1002/2015jg002974mentioning
confidence: 99%
“…Overall, FPM harbored a complex microbiota, because the high Shannon index (5.61 to 6.96) detected in highquality FPMs (data not shown) was comparable to that (5 to 7) in some soils at a sequencing depth of 4,000 to 9,000 reads (32). Compared to about 16 phyla detected in FPMs in previous studies (7,8), 33 phyla detected in this work might expand our understanding of the phylogenetic status of an enormous number of uncultured microbes in this ecosystem.…”
Section: Discussionmentioning
confidence: 91%